I have no idea what to do here.

[f(2)-f(1)]-[f(1)-f(0)]
f(s)=s^2-6s-9

1 answer

The "s" in f(s) is just a place holder. To evaluate f(2), just replace every "s" with a "2" and then simplify it all.

To save yourself some work, note that
[f(2)-f(1)]-[f(1)-f(0)]
= f(2)-f(1)-f(1)+f(0)
= f(2)-2f(1)+f(0)
so, [f(2)-f(1)]-[f(1)-f(0)]
= (2^2-6*2-9) - 2(1^2-6*1-9) + (0^2-6*0-9)
= (4-12-9) - 2(1-6-9) + (-9)
= -17 - 2(-14) - 9
= -17+28-9
= 2
Similar Questions
  1. which phrase describes a claim that is "debatable"?a an idea about a topic that is not grounded in evidence b an idea that is
    1. answers icon 1 answer
  2. Which phrase describes a claim that is "debatable"? (1 point)an idea that can be supported by facts an idea that is open to
    1. answers icon 1 answer
  3. Develop a feasible business idea by answering the following questions:1.1Choose a business idea: Select an idea that you believe
    1. answers icon 1 answer
  4. Which of the following describes the central idea of a story?A. an idea that connects the story to other stories B. an idea that
    1. answers icon 3 answers
more similar questions